Electrochemical Reductive Dehalogenation of ortho-Halogenated Phenols on Ag Electrode by in situ FTIR - Yi, Jingmiao; Lu, Jinjin; Shi, Xiaohong; song, Dandan; Zhao, Weijuan; Li, Meichao (Asian Journal of Chemistry, 2014)
Electrochemical reductive dehalogenation reactions of ortho-halogenated phenols, namely, o-iodophenol (OIP), o-bromphenol (OBP) and o-chlorophenol (OCP) on Ag electrode in alkaline medium have been studied by in situ FTIR combined with cyclic voltammetry and computational calculations. The Ag electrode showed a high electrochemical activity for dehalogenation reactions of OBP and OIP in contrast with OCP under the similar conditions and the dehalogenation potential of OIP was more positive than OBP, reflecting more facile reduction of OIP on Ag electrode. On the basis of in situ FTIR of OCP on Ag electrode, it was not obvious and the electrochemical reduction reaction was quite weak. Therefore, the order of electrochemical reductive dehalogenation was OIP > OBP > OCP.